2020
DOI: 10.1097/wno.0000000000001051
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Telehealth Adoption by Neuro-ophthalmologists During the COVID-19 Pandemic: Benefits, Barriers, and Utility

Abstract: Background: During the COVID-19 pandemic, telehealth modalities have come to prominence as a strategy for providing patient care when in-person care provision opportunities are limited. The degree of adoption by neuroophthalmologists has not been quantified. Methods: Telehealth utilization pre-COVID-19 and peri-COVID-19 was surveyed among practicing neuroophthalmologists in and outside the United States using an online platform. Demographics, perceived benefits, barriers, and utility for different neuro-ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 13 publications
3
74
0
Order By: Relevance
“…Peri-COVID, telehealth has been an important alternative not only for the underserved but also for the elderly, immunocompromised, mobility-restricted, and visually impaired patients. The main barriers to implementation cited by telehealth adopters and nonadopters include concerns about data/physical examination quality, reimbursement, medical liability, and sufficient infrastructure support for implementation (41).…”
Section: Aspects Specific To Neuro-ophthalmology Workforcementioning
confidence: 99%
See 1 more Smart Citation
“…Peri-COVID, telehealth has been an important alternative not only for the underserved but also for the elderly, immunocompromised, mobility-restricted, and visually impaired patients. The main barriers to implementation cited by telehealth adopters and nonadopters include concerns about data/physical examination quality, reimbursement, medical liability, and sufficient infrastructure support for implementation (41).…”
Section: Aspects Specific To Neuro-ophthalmology Workforcementioning
confidence: 99%
“…A survey of pre–COVID-19 and peri–COVID-19 telemedicine utilization in neuro-ophthalmology found that an additional 64% of neuro-ophthalmologists adopted video telehealth visits. Respondents cited benefits including ensuring continuity of care, improving patient access to care, and patient convenience ( 41 ). Respondents also increased adoption of asynchronous telehealth models, including remote interpretation of tests, second opinion record review, and interprofessional consultations.…”
Section: Changes In Telehealth Since the Pandemicmentioning
confidence: 99%
“…There are acknowledged challenges to telegenetics consultations, including the inability to perceive patients' nonverbal cues, difficulty performing psychosocial counseling, technology‐related issues, and reimbursement limitations, leading to a historic provider preference for an in‐person model of health care delivery (Terry et al, 2019; Zierhut et al, 2018; Zilliacus et al, 2010). These barriers are not unique to telegenetics as they have been experienced by many healthcare providers exploring telehealth across various specialties (Burke Jr. & Hall, 2015; Dinesen et al, 2016; Moss, Lai, & Ko, 2020). However, genetic counselors in New York State (NYS) and 23 other states are further challenged because they do not have licensure (as of October 2020), which presents an added limitation to providing services to patients in need ("States Issuing Licensing for Genetic Counselors," 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of specialists used phone consultations, whilst ~10% employed video calls. A survey of American neuro-ophthalmologists noted a 64.4% increase in telehealth video consults [ 61 ]. This survey identified ease of access, continuity and efficiency of care as benefits and specifically highlighted the challenges in the detection and management of conditions requiring funduscopic examination as a barrier.…”
Section: Main Textmentioning
confidence: 99%